2008
DOI: 10.1002/app.28483
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of maleated natural rubber by precipitated silica

Abstract: Graft copolymers of maleic anhydride and natural rubber or so-called maleated natural rubbers (MNRs) were prepared in a molten state with varying maleic anhydride contents from 4 to 10 phr. In this work, the filler-filler and filler-rubber interactions of the MNR and precipitated silica were investigated. The MNR compounds containing 40 phr of silica both with and without 9 wt % of silane coupling agent were prepared. By increasing the maleic anhydride contents, the Mooney viscosity and cure times were increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 18 publications
6
27
0
1
Order By: Relevance
“…ese chemical bonds between W-ST and NR improved filler-rubber interaction of NR composites. Similar results were found by Jacob et al [1], Ismail et al [26], and Sahakaro and Beraheng [27]. ey suggested that the prolonged scorch time and cure time of NR composites resulted from the better interaction between the filler and rubber matrix.…”
Section: Characterization Of Rhf/nrsupporting
confidence: 79%
“…ese chemical bonds between W-ST and NR improved filler-rubber interaction of NR composites. Similar results were found by Jacob et al [1], Ismail et al [26], and Sahakaro and Beraheng [27]. ey suggested that the prolonged scorch time and cure time of NR composites resulted from the better interaction between the filler and rubber matrix.…”
Section: Characterization Of Rhf/nrsupporting
confidence: 79%
“…It is interesting to note that at the optimum MA concentration, the tensile strength of the compatibilized blend is equal to that of NR even when the blend contains 5% EPS. The succinic anhydride groups grafted onto NR and EPS molecules enhance the polarity of the blend and an interaction between the succinic anhydride groups and the hydroxyl groups on silica surface is quite likely [36]. Similar interactions between the hydroxyl and maleic anhydride groups have previously been proposed such as in the cases of PP-g-MA versus nano-silica [38] and maleated NR versus paper sludge filler [39].…”
Section: Cure Characteristicssupporting
confidence: 55%
“…The interfacial tension reduces thereby improving adhesion between the components as well as between the filler and the polymer matrix which enhances the tensile strength of the blends [12,15]. Moreover, it has been reported that silica filled NR shows better properties on MA grafting [36]. The modulus at 300% Fig.…”
Section: Cure Characteristicsmentioning
confidence: 97%
“…In order to enhance the silica dispersion, many efforts have been carried out with silica surface modification in recent years . The other end silane grafted NR and maleic anhydride grafted NR were used as compatibilizers in silica filled green composites . Small angle X‐ray scattering (SAXS) techniques are very suitable for the study of filler morphologies in silica‐filled rubber compounds .…”
Section: Introductionmentioning
confidence: 99%